Pengenalan Digital Marketing Dalam Upaya Pengenalan Objek Wisata Hutan Pinus Di Buntu Datu - Olivia Devi Yulian P; Astriwati Biringkanae; Stefani Marina Palimbong (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
Digital marketing in the current era has become very important in marketing its products, no exception to tourism. Social Media allows everyone to create and spread their own content on various social networking platforms. But in the promotion of tourism, there needs to be a briefing on the strategy of using and preparing content, including social media ethics for managers and other stakeholders. Based on this, the PKM team conducted digital marketing introduction and training activities to be able to promote Pinus Buntu datu Forest Tourism and what potential it has and can be introduced to tourists. This training is aimed at tourism managers of Pinus Buntu datu Forest and the interest of the participants is quite high and they also feel the benefits of this digital marketing introduction training can be applied in digital marketing on social media. Further training is still needed on how to create messages in multimedia (photos and videos) that are attractive to potential tourists.